Penerapan Metode Awareness-Trial-Reinforcement dalam Unggah Konten Instagram pada Akun Kedai Ruang Kopi - Mardani, Muhammad Alif Athalla; Pujianto, Totok; Syahmurman, Faizal; Ardiansah, Irfan (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2023)
Marketing in the era of the development of social media is important for developing a business. Kedai Ruang Kopi is a food and beverage sales service business (coffeeshop), especially coffee and snacks. Kedai Ruang Kopi uses social media Instagram with the account @kedaikopiruang which is not optimal compared to other similar business accounts due to the lack of awareness of Kedai Ruang Kopi on marketing strategies. This study aims to optimize the use of Kedai Ruang Kopi (@kedaikopiruang) accounts to increase their insights using the A-T-R (awareness-trial-reinforcement) method. The principle of applying the A-T-R method is through creation to raise consumer awareness so that there is an act of trying, then followed by efforts to strengthen or confirm so that finally the product is trusted. Evaluation of the A-T-R method uses data insights and interviews with sample consumers. The results showed that there was an increase in insights into the @kedaikopiruang account, namely followers by 16.8%, accounts reached by 20%, and an increase in accounts engaged by 60%. The results of interviews with 56 samples showed that 17% of the sample consumers came because they saw Kedai Ruang Kopi's Instagram account. The number of sales of Kopi Ruang Shop increased until May 2023 but decreased in June 2023 due to several undetermined factors. Based on the results above, the marketing strategy implemented on @kedaikopiruang is still considered unsatisfactory when compared to other similar accounts.